Obstacles To The Investigation Process In The Military Justice System Related To Ankum's Authority As Investigator - Wijaya Ardi (Jurnal Hukum Khaira Ummah, 2021)
The purpose of this research isto analyze the obstacles to the investigation process by Military Police investigators and/or Otmil faced with Ankum's role as an investigator in resolving cases of TNI soldiers. This legal research is a normative juridical research using the Act as the primary legal material. The Military Justice System has three investigator components, namely superiors who have the right to punish (Ankum), Military Police (Pom), Military Oditur (Otmil). Ankum as a criminal investigator is regulated in Article 69 paragraph (1) of Law No. 31 of 1997 concerning Military Courts. Law enforcement in the military justice environment sometimes encounters obstacles, with the large authority of the unit commander as Ankum. The conclusion from this paper is that the obstacles that are often faced are:by investigators of the Military Police and/or Otmil faced with Ankum's role as an investigator in resolving cases of TNI soldiers, among others, a conflict of authority in the investigation process, a conflict of norms in determining the detention of a suspect, Ankum does not meet the formal requirements as an investigator, Ankum tends to defend his subordinates and the investigation takes a relatively long time due to bureaucratic problems. The solution to this problem must be an amendment to the Military Court Law so that there is clear certainty about Ankum's authority in resolving criminal cases committed by soldiers under his command to provide legal certainty for all parties.